A Novel Transcriptional Regulator Related to Thiamine Phosphate Synthase Controls Thiamine Metabolism Genes in Archaea - Rodionov, Dmitry A. (J Bacteriol, 2017)
Thiamine (vitamin B(1)) is a precursor of thiamine pyrophosphate (TPP), an essential coenzyme in the central metabolism of all living organisms. Bacterial thiamine biosynthesis and salvage genes are controlled at the RNA level by TPP-responsive riboswitches. In Archaea, TPP riboswitches are restricted to the Thermoplasmatales order. Mechanisms of transcriptional control of thiamine genes in other archaeal lineages remain unknown. Using the comparative genomics approach, we identified a novel family of transcriptional regulators (named ThiR) controlling thiamine biosynthesis and transport genes in diverse lineages in the Crenarchaeota phylum as well as in the Halobacteria and Thermococci classes of the Euryarchaeota. ThiR regulators are composed of an N-terminal DNA-binding domain and a C-terminal ligand-binding domain, which is similar to the archaeal thiamine phosphate synthase ThiN. By using comparative genomics, we predicted ThiR-binding DNA motifs and reconstructed ThiR regulons in 67 genomes representing all above-mentioned lineages. The predicted ThiR-binding motifs are characterized by palindromic symmetry with several distinct lineage-specific consensus sequences. In addition to thiamine biosynthesis genes, the reconstructed ThiR regulons include various transporters for thiamine and its precursors. Bioinformatics predictions were experimentally validated by in vitro DNA-binding assays with the recombinant ThiR protein from the hyperthermophilic archaeon Metallosphaera yellowstonensis MK1. Thiamine phosphate and, to some extent, TPP and hydroxyethylthiazole phosphate were required for the binding of ThiR to its DNA targets, suggesting that ThiR is derepressed by limitation of thiamine phosphates. The thiamine phosphate-binding residues previously identified in ThiN are highly conserved in ThiR regulators, suggesting a conserved mechanism for effector recognition. IMPORTANCE Thiamine pyrophosphate is a cofactor for many essential enzymes for glucose and energy metabolism. Thiamine or vitamin B(1) biosynthesis and its transcriptional regulation in Archaea are poorly understood. We applied the comparative genomics approach to identify a novel family of regulators for the transcriptional control of thiamine metabolism genes in Archaea and reconstructed the respective regulons. The predicted ThiR regulons in archaeal genomes control the majority of thiamine biosynthesis genes. The reconstructed regulon content suggests that numerous uptake transporters for thiamine and/or its precursors are encoded in archaeal genomes. The ThiR regulon was experimentally validated by DNA-binding assays with Metallosphaera spp. These discoveries contribute to our understanding of metabolic and regulatory networks involved in vitamin homeostasis in diverse lineages of Archaea.